IDENTIDADES DE RAÇA, DE GÊNERO E DE SEXUALIDADE NAS AULAS DE LÍNGUA INGLESA NA VISÃO DAS/OS ESTUDANTES - Sene, Rosana Aparecida Ribeiro de (2017)
The reflections brought here are relevant to the study of speech with regard to foreign languages, more specifically English, approaching the identities of genre, race and sexuality. The research was carried out in the “Zumbi dos Palmares” State School, in the town of Prudentópolis- PR, in a class of the second year of High School. It aims at investigating how the pupils perceive the issues of genre, race and sexuality in the school environment, and understanding why we should discuss such identities in the English lessons, from the students’ perspective. The research answered to the questions: how do students perceive the identities of race, genre and sexuality in the English lessons? And yet, what are the reasons for discussing the identities of race, genre and sexuality in the English lessons, from the students’ perspective? The research was based on the theoretical references of social identities of race by: Ferreira (2006, 2014, 2012, 2015), Gomes (2005), Hall (2003), Carone (2002), Bento (2002), Cavalleiro (2014), and Melo (2015). For social identities of genre the reference was: Louro (1997, 2008, 2007, 2000, 2009, 2013), Scott (1995), Auad (2003, 2006), Beauvoir (1970), Garcia (2011). And as for sexuality: Miskolci (2012), Weeks (2000), Butler (2000, 2010), Salih (2013), Furlani (2012), and Nelson (2015). Theoretical reference was also used for the issues of identities and the teaching of the English language: Moita Lopes (2002, 2006), Hall (2011), Woodward (2013), Silva (2013), Dias and Mastrella-Andrade (2015), Cruz (2015), Jorge (2014), and Pereira(2014). The method employed is qualitative research of the ethnographic type, case study with theoretical backing in André (1995), Bortoni-Ricardo (2008), and Yin (2001), making use of the following tools of data generation: a questionnaire, autobiographical narrative, interview of focus group and field diary, with basis on Marconi (1990), Menga and André (1986), Gatti (2005), and Barbour (2009). The analyses on this research demonstrate that the school curriculum is still very conservative, keeping the identities white, heterosexual and male as the ideal representation in the school environment, disregarding or minimising suffering, inequality, prejudice, racism, homophobia, and sexism of the least represented identities concerning the issues of genre, race and sexuality. Besides, it was possible to observe that the school silencing before the questions of genre, race and sexuality causes serious consequences to the students, such as: isolation, racism, racial prejudice, depression, homophobia, anxiety, low self-esteem, feelings of inferiority, exclusion, denial of oneself, lack of understanding, physical, verbal and psychological violence , and disputes between male and female, where the male is outstanding as compared to the female. The analyses also demonstrate that some pupils try to take action to break off the standard “rules” supported by the school. They show themselves brave when taking on their identities of genre, race and sexuality in this environment. However, because of the existing power inside such school environment, at the moment of confrontation to keep the “order” or to support the new possibilities of people’s experience, in most of the times, the “rule” prevails in the end. This way, in order to help destabilize the “rule”, it becomes necessary to “empower” the issues of genre, race and sexuality. In view of this, the English language can be used as a major instrument to build up meaning in the social practices, deconstructing the formation of the binarism: man/woman, black/white, eterosexual/homosexual, in the educational environment, contributing to the construction of a more humane society.